Looking like David or Goliath? Cultural differences in display of competence in competitive situation - Chan, Lynette Yi Ling (2015)
In competitions, people often disclose information about themselves to their opponents in strategic ways. This study examined this very process, focusing on how the strategic display of competence in competitive contexts may vary across cultures. Through experimentally examining preferences for authenticity norms, cross-cultural difference in competency display among biculturals was found within a competitive situation. A two-pronged priming methodology – use of cultural images and language - was adapted. Firstly, results found increase accessibility of assigned culture to each group, suggesting experimental success in manipulation of culture. Secondly, author also found within a competitive situation, those primed with independent self- construal preferred advertising their strengths whereas those primed with interdependent self-construal displayed scores closer to their core selves. These preliminary findings supported the account of culture-situation interaction in affecting one’s authentic self-expression. Future research on possible mediating factors and methodology convergence were suggested. Lastly, practical implications of the culture-situation fit were also discussed.